‘One Does Everything to Make Life Better.’ Petty Corruption and Its Legal Implications in Hungary - Burai Petra (Comparative Southeast European Studies, 2018)
Combining research into the law with the conceptual framework offered by legal anthropology contributes to a more thorough understanding of how individuals experience corruption and anti-corruption legislation. Interviews with elderly Hungarians allow a deeper understanding of traditions and individual behaviour that influence the implementation of anti-corruption law. Informal payments in health care, in the realm of petty or everyday corruption, have become social traditions based on a general faith in their ability to organize and determine social and individual relations. At the same time, they have turned out to be exceptional challenges as far as their legal adjudication is concerned, as individuals are keen to find stability and reliability in norms, traditions and personal relationships outside the scope of the law.